Spatial transcriptomics reveals an unexpected impact of tau and tau pathology on the expression of transthyretin - Croteau, Deborah L.; Navarro, Jose Fernandez; Comptdaer, Thomas; Andrusivova, Zaneta; Jurek, Aleksandra; Bonnefoy, Eliette; Buée, Luc; Bohr, Vilhelm A.; Lundeberg, Joakim; Galas, Marie-Christine (Frontiers in Aging Neuroscience, 2025)
IntroductionRNA expression is modulated by tau. We used two mouse models, THY-Tau22 mice, which express pro-aggregation tau, and TauKO mice, which are null for tau, to improve our understanding of tau-altered mRNA expression in brain.MethodsSpatial transcriptomics on Tau22 and TauKO mice were used to interrogate regional mRNA expression changes. We focused on mRNA expression changes in the hippocampus and ventricles; two regions altered early in Alzheimer’s disease.ResultsWe identified the transthyretin mRNA, Ttr, as being dysregulated in a tau-dependent manner. Immunofluorescence (IF) revealed increased TTR protein expression in THY-Tau22 mice and lowered expression in TauKO mice in the choroid plexus epithelial cells.ConclusionAs TTR is involved in the clearance of Aβ and the prevention of Aβ aggregation, we evaluated endogenous mouse Aβ in TauKO mice and observed increased Aβ deposits. Our study reveals a hitherto unknown regulatory role of tau on Ttr mRNA and protein expression, which may participate in a feedback loop contributing to Aβ disease progression.